Down’s Syndrome and Craniovertebral Instability: Topic Review and Treatment Recommendations - Brockmeyer, Douglas (Nepal Journal of Neuroscience, 2005)
Down’s syndrome, is the most common inherited chromosomal disorder in humans occurring in 1.5 in every 1,000 live births and is characterized by multiple neurological as well as nonneurological abnormalities. The issue of craniovertebral instability in Down’s syndrome patients is a very controversial topic. Multiple studies and editorials have been written over the last two decades and much of the information is conflicting and confusing. The goal of this review is to provide a rational synthesis of this previous work and provide recommendations by which parents of Down’s syndrome patients, pediatricians, family practitioners and other health professionals may make intelligent choices regarding screening of Down’s syndrome patients. It is a second goal of this review to synthesize the surgical data on this topic and provide recommendations for anesthesiologists, otolaryngologists, orthopedic surgeons and neurosurgeons. Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, Page: 52-58